2019
DOI: 10.3389/fnins.2019.01306
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Contractility of Rat Brain Pericytes in Conditions That Mimic Stroke; an in vitro Study

Abstract: Reopening of the cerebral artery after occlusion often results in “no-reflow” that has been attributed to the death and contraction (rigor mortis) of pericytes. Since this hypothesis still needs to be confirmed, we explored the effects of oxygen glucose deprivation (OGD) on viability and cell death of primary rat pericytes, in the presence or absence of neurovascular unit-derived cytokines. Two morphodynamic parameters, single cell membrane mobility (SCMM) and fractal dimension (Df), were used to analyze the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…However, Smyth et al ( 2018 ) showed some αSMA expression on junctional pericytes in vivo, while Alarcon-Martinez et al ( 2018 ) showed that capillary pericytes do express αSMA which rapidly depolymerizes during tissue fixation thus evading detection by immunolabeling. While we showed that HBVPs had heterogeneous αSMA expression, expression of αSMA in in vitro pericytes has been shown previously, which may be due to upregulation of αSMA expression in culture conditions (Heyba et al 2019 ; Smyth et al 2018 ). Here, we only assessed whether pericyte subtypes had differing motility and contractility, and further analysis of other pericyte functions such as BBB integrity, immune activity and susceptibility to cell death would need to be carried to determine the full scope of functional heterogeneity between morphological subtypes of pericytes, and whether there was an association with an in vivo subtype.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, Smyth et al ( 2018 ) showed some αSMA expression on junctional pericytes in vivo, while Alarcon-Martinez et al ( 2018 ) showed that capillary pericytes do express αSMA which rapidly depolymerizes during tissue fixation thus evading detection by immunolabeling. While we showed that HBVPs had heterogeneous αSMA expression, expression of αSMA in in vitro pericytes has been shown previously, which may be due to upregulation of αSMA expression in culture conditions (Heyba et al 2019 ; Smyth et al 2018 ). Here, we only assessed whether pericyte subtypes had differing motility and contractility, and further analysis of other pericyte functions such as BBB integrity, immune activity and susceptibility to cell death would need to be carried to determine the full scope of functional heterogeneity between morphological subtypes of pericytes, and whether there was an association with an in vivo subtype.…”
Section: Discussionsupporting
confidence: 61%
“…Given that standard pericytes make up the majority subtype in HBVP cultures, this may explain why contraction and relaxation still occurred in whole-well assays (Neuhaus et al 2017 ). However, some sub-population differences within cultured pericytes for Ca 2+ release (Halaidych et al 2019 ) and cell contraction (Heyba et al 2019 ) were observed following ET1 stimulation. We then explored whether there were differences in αSMA expression between morphological subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This extended period of contractility has been previously associated with calcium handling, with shown to induce increases in intracellular calcium intracellular in numerous tissue types including podocyte(Edwards & Pallone, 2008; Burdyga & Borysova, 2014; Binz-Lotter et al ., 2020), with a pronounced increase in intracellular calcium associated with elevated frequency of pericyte contractility(Hirunpattarasilp et al ., 2022). Additionally, in neurodegenerative states, pericytes can enter a state of ‘rigor’ to induce a permanent state of capillary constrict post-pericyte death (Yemisci et al ., 2009; Hall et al ., 2014 b ; Heyba et al ., 2019), a process dependent upon pericyte intracellular calcium handling(Korte et al ., 2022). This implies AngII induced pericyte activation of AT1 is fundamental in the regulation of spinal cord capillary tone.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and culture of RBPs were performed by subculturing of primary endothelial cells isolated by the protocol by M Heyba et al. ( 38 ). Afterward, cells were immunostained for PDGFRb as a positive pericytic marker.…”
Section: Methodsmentioning
confidence: 99%